Novel Choices of Cannula for Blood Delivery via Femoral Artery in Pediatric Patients - Yamamoto, Tomohiro; Saito, Takeshi; Shiraishi, Shuichi; Asfour, Boulos; Hraska, Victor; Schindler, Ehrenfried (The Thoracic and Cardiovascular Surgeon, 2020)
We previously presented a cardiopulmonary bypass (CPB) method with blood delivery via femoral artery cannulation for pediatric aortic arch repair operations using the Radifocus Introducer sheath. However, the flow rate with the Radifocus Introducer sheath is limited by accessory parts with the same structure having a smaller inner diameter among different sizes, rather than the sheath body. Therefore, we further devised a combination of the JELCO IV catheter, an extension tube, and a three-way stopcock with a larger opening to obtain more flow rate keeping the CPB circuit pressure significantly lower than when using the Radifocus Introducer sheath successfully.
Keywords: cardiopulmonary bypass CPB; femoral artery cannulation; flow rate; CPB circuit pressure; alternative cannula system